Extracellular enzymes produced by bacteria isolated from mrine invertbrates - León, Jorge (2000)
In order to select marine bacteria with the ability to produce extracellular enzymes (EEC), samples from Argopecten purpuratus and Crassostrea gigas in cultivation as well as from other interticlal and benthic invertebrates were analyzed. The selection of producer EEC strains was carried out in Marine Agar (MA) with addition of the relevant substratum (starch, casein, tween-80, lecithine, DNA and gelatine). The EEC producer strains evaluation was carried out on 102 isolates. The results show that bacteria associated toA. purpuratusand C. gigashave the best multienzymatic activities; however, Semimytilus algosus, Tetrapigus niger and Thais chocolata are also important sources of bacteria producers of EEC. The qualitative multienzymatic activity in MA (clear or opaque zones around the colonies in mm of diameter) varied from 6 to > 16 mm. The frequency of multienzymatic production was caseinase 62,74%, tween-esterase 57,84%, amylase 52,94%, gelatinase 38,23%, DNAse 33,3%, agarase 5,43% and lecithinase 90,0%. The results suggest the possibility of using native strains for biotechnological purposes.